Investigating the sound power level of a simplified underwater vehicle induced by flow separation. (15th May 2020) - Rui, Deng; Zezhen, Zhang; Fuzhen, Pang; Tiecheng, Wu; Wanzhen, Luo
Abstract: Fluid flowing along underwater vehicles often acquire unsteady flow types such as flow separation and vortex shedding. The characteristics of unsteady flows around the underwater vehicle cause high frequency fluctuating pressure and noise on the vehicle rendering the underwater vehicle easily exposed. Studying the characteristics of flow separation on underwater vehicles, establishing accurate prediction methods for flow-induced noise and fast prediction formula based on test and simulation data are important for better understanding of the mechanism of flow separation-induced noise as well as fast prediction and control of underwater noise. In this study, the flow separation characteristics and fluctuating pressure induced by flow separation of underwater vehicles are studied. A simplified model composed of a cylinder, cone and other simple geometry is taken as the research object for water tunnel test and numerical analysis. We also discuss the appropriate numerical simulation method for predicting the flow separation and fluctuating pressure. The vortex distribution characteristics and flow separation mechanisms around the vehicle are analyzed and described based on the numerical method. The fitting function of pressure at different positions is established based on the flow characteristics, the experimental and numerical prediction data. Subsequently, the prediction formula of sound power level is verified. Results show that the flow separation characteristics and the numerical strategy employed in this study efficiently captured the flow filed and the surface fluctuating pressure characteristics of the simplified underwater vehicle. Findings from the numerical results and water tunnel data showed good prediction accuracy. The prediction results reflected the varying relationship of amplitude, frequency and the trend of data distribution. Highlights: A simplified underwater vehicle model is taken as the research object for water tunnel test and CFD analysis. The vortex distribution characteristics and flow separation mechanism around the vehicle were analyzed and described based on the LES method. A prediction function system that can predict the sound power level of underwater vehicles rapidly and accurately is obtained.